THE ECONOMIC AND ENVIRONMENTAL PERFORMANCES OF AGROFORESTRY LAND-USE MODELS IN DAK NONG PROVINCE - Thi Minh Nguyet, Bui; Van Quy, Khuc; Nguyen Khang, La; Sy Doanh, Le; Quang Huy, Nguyen (Journal of Forestry Science and Technology, 2019)
We studied the economic and environmental performance of different types of land-use models inside and outside forestland in the Central Highlands of Vietnam. We used a semi-structured interview method, descriptive statistical methods, a structural model, and a matching method to obtain and analyze data from 414 plots at 31 communes in Dak Nong province. Six agroforestry land-use models were investigated at the study site, including pure industrial crops (coffee), pure fruit trees (Passiflora edulis), pure plantation forests (Acacia Mangium), intercropping of industrial plants and fruit trees, intercropping of industrial and forestry trees, and short-term crops (Cassava). On forestland, the agroforestry land-use models yield fewer economic and environmental outcomes than those on agricultural land. The pure industrial tree becomes the most popular agroforestry land-use model, yet it produces fewer outcomes in relation to the remaining models. The top three land-use models are (1) pure fruit tree, (2) intercropping of industrial plants and fruit trees, and (3) intercropping of industrial and forestry trees. The empirical findings illustrate some policy implications for achieving further sustainable development associated with the effective agroforestry land-use models in Dak Nong province.